2021
DOI: 10.1111/inm.12942
|View full text |Cite
|
Sign up to set email alerts
|

Chronicling moral distress among healthcare providers during the COVID‐19 pandemic: A longitudinal analysis of mental health strain, burnout, and maladaptive coping behaviours

Abstract: The COVID‐19 pandemic has presented many novel situations that have amplified the presence of moral distress in healthcare. With limited resources to protect themselves against the virus and strict safety regulations that alter the way they work, healthcare providers have felt forced to engage in work behaviours that conflicted with their professional and personal sense of right and wrong. Although many providers have experienced moral distress while being physically in the workplace, others suffered while at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 97 publications
(228 reference statements)
5
50
0
10
Order By: Relevance
“…The association with depression is consistent with findings in military personnel [52][53][54]. One longitudinal study identified burnout as a predictor of MD [20]. This implies that persons with preexisting psychological problems are more vulnerable to MD than others.…”
Section: Consequences Of Moral Distress and Moral Injurysupporting
confidence: 84%
See 4 more Smart Citations
“…The association with depression is consistent with findings in military personnel [52][53][54]. One longitudinal study identified burnout as a predictor of MD [20]. This implies that persons with preexisting psychological problems are more vulnerable to MD than others.…”
Section: Consequences Of Moral Distress and Moral Injurysupporting
confidence: 84%
“…The relative normativity of experiencing moral stressors [28] is in accordance with the fact that some of the COVID-19 studies report low and medium levels of MD [14][15][16]25], and by this, they do not differ from results of pre-COVID-19 studies in HCWs [32,61]. Nevertheless, many HCWs have continuously experienced morally stressful situations during the pandemic [15,20]. We consider this comparable to cumulative traumatization.…”
Section: Moral Distress and Moral Injury During Covid-19supporting
confidence: 69%
See 3 more Smart Citations